The effect of Breast Reconstruction surgeries on Self- Esteem among breast cancer women after total mastectomy (Journal of Hama University, 2025)
Introduction: Self-esteem (SE) is considered an important and essential aspect after breast cancer surgery for breast cancer patients (Breast Cancer BC), especially those who underwent breast reconstruction surgery (Breast Reconstruction Surgery BRS), Since the nursing role is an important part of the physical and psychological health care of breast cancer patients, through assessment, planning, and continuous care during the treatment period of all kinds, especially the psychological aspect of surgical patients. Purpose of Study: The present study aimed to evaluate SE in BC patients before surgery and 2 weeks after end-stage BRS, Methods: Study included 30 women were selected using a convenience sampling method, and data were collected using a pre-prepared questionnaire in several specialized surgical clinics in Latakia Governorate before surgery and two weeks after the end-stage of BRS. Result: The results showed that BRS surgery improves their SE, as it showed a statistically significant increase in average self-esteem (P = 0.022) by 4 degrees two weeks after surgery. Conclusion: The study recommended the necessity of conducting training and educational courses for nurses working in surgical and oncology departments to evaluate SE for BRS patients, and the importance of conducting other future research to evaluate SE on a larger sample and at different time periods, in addition to studying nursing interventions that can improve SE, which reflects positively on the physical and psychological condition. For BC female patients.
Keywords: Breast Cancer, Total Mastectomy, Breast Reconstruction surgery, Self Esteem -